(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study aims to analyze the role of placenta VEGF level using immunocytochemical techniques and comparing the obtained results with PAS FIGO grading. This retrospective cross sectional study on total sampling of formalin fixed paraffin-embedded tissue from placenta sampling of elective surgery which were diagnosed as PAS. Sample were immunostained using VEGF and semi-quantitatively Immuno Reactive Score (IRS) measured based on modified Remmele scale index. The result obtained 32 samples that meet inclusion criteria which are found into grade I (n=5), grade II (n=11) and grade III (n=16). This study showed average VEGF at grade I (4.68±1.03), grade II (3.81±1.41), grade III (4.46±1.82) and no significant difference of VEGF expression between grade I, grade II and grade III (p = 0.264). Intraplacental VEGF do not describe the severity of PAS FIGO grading.